Biofunctional characteristics of banana peel dietary fibre (BPDF) and its associated in vitro antidiabetic properties - Zaidan, Uswatun Hasanah; Ghani, N. L. A.; Zahari, N. S.; Rahim, M. B. H. A.; Gani, S. S. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
The potential applications of banana peel waste can resolve environmental issues; however, the potentials of banana peels as antidiabetic remain unexplored. Therefore, the present work was carried out to investigate the biofunctional and surface properties of banana peel dietary fibre (BPDF) and its enzyme inhibitory activities. The water holding capacity (WHC), oil holding capacity (OHC), swelling capacity (SC), and glucose absorption capacity (GAC) were measured, and the glucose retardation index (GDRI) was analysed. The inhibitory effect of BPDF against α-amylase activity was also observed. The findings showed that the WHC (0.7 g/g), OHC (0.3 g/g), SC (0.73 mL/g), GDRI (6.58 - 31.72%), and GAC (0.162 - 19.211 mmol/g) of BPDF could have the potential in regulating diabetes, and explain the physiological effects of dietary fibre. The surface morphology of BPDF was analysed using scanning electron microscope. Interestingly, BPDF hampering effects on the diffusion of glucose through α-amylase inhibitory activity with IC50 8.9 µg/mL was found to be comparable to acarbose (IC50 8.6 µg/mL), thus showing potential in lowering postprandial blood glucose (type 2 diabetes mellitus).